Loan Origination System Implementation Model and Credit Business Process Value Creation in Improving Business Performance - Nasution, Harmansyah; Rahayu, Agus; Gaffar, Vanessa; Sofia, Alfira; Yulianto, Erwin (Universitas Dharma Wacana, 2024)
The banking industry as a credit provider has changed substantially over the last century, namely that when a bank will lend money with collateral as collateral, the process is carried out in stages involving many bank officers. Currently, almost all operating financial institutions have been digitized, especially the credit application process. More and more customers are choosing digital loans over traditional loans because of the benefits they provide. The aim of this research was to analyze the picture of Business Performance which includes Customer Requirements, Digital Leadership, Loan Origination System Implementation and Credit Business Process Value Creation which influence it. The research method uses quantitative research with descriptive and verification research types. The research population was 64 branch offices which were the analysis units using a saturated sampling technique. The research instrument uses a questionnaire and data analysis techniques to determine the correlative relationship in this research using Partial Least Square. The research results show that Business Performance with the dominant dimension, namely Financial Performance, is influenced by Loan Origination System Implementation with the dominant dimension, namely Document Management and Credit Business Process Value Creation with the dominant dimension, namely Responsiveness. Loan Origination System Implementation and Credit Business Process Value Creation are influenced by Customer Requirements with the dominant dimension, namely Customer Expectation and Digital Leadership with the dominant dimension, namely Customer Focused.